PENERAPAN TATA RUANG DALAM GALERI SELASAR SUNARYO ART SPACE - Bandhawa, Raga Anggaraksa; Agustin, Dyan (Universitas Medan Area, 2024)
A gallery is a place or building that is intended as a place for the exhibition of artworks and other art activities. Space will be an important aspect in the arrangement of a gallery building because it certainly supports the arrangement and appearance of each work of art. Selasar Sunaryo Art Space (SSAS) is a gallery established with the aim of supporting the development of practice, art studies, and culture in visual form in Indonesia. SSAS is one of the gallery cultural centers visited by every circle in Indonesia so that the role of architecture in buildings is needed to support art activities in it. This makes SSAS an interesting object to research in the aspect of spatial arrangement. Therefore, this study aims to determine the spatial pattern in the gallery as an art activity facility. The research was conducted using qualitative methods through direct survey and secondary data review from other journal references. The observation results show that the inner spatial pattern of SSAS is made related between spaces so that the circulation pattern created becomes flexible for users.